2008
DOI: 10.1097/hjh.0b013e328313e547
|View full text |Cite
|
Sign up to set email alerts
|

Telmisartan prevents aneurysm progression in the rat by inhibiting proteolysis, apoptosis and inflammation

Abstract: The angiotensin II type 1 receptor antagonist, telmisartan, prevents abdominal aortic aneurysm progression independently of blood pressure reduction by inhibiting proteolysis, apoptosis and inflammation in aortic tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 40 publications
1
40
0
Order By: Relevance
“…13 In addition, activated caspase-9, the key initiator of the intrinsic pathway, was documented in experimental aneurysm, 14 further supporting the presence of mitochondrial-dependent apoptosis during aneurysm development. The integral relationship between SMC apoptosis and aneurysm is further demonstrated by studies in which apoptosis was attenuated by experimental approaches such as the removal of mast cells, 14 blockage of the angiotensin II (Ang II) signaling, 15 and inhibition of Rho GTPase. 16 However, whether and how SMC apoptosis contributes to aneurysm formation has not been directly addressed.…”
mentioning
confidence: 99%
“…13 In addition, activated caspase-9, the key initiator of the intrinsic pathway, was documented in experimental aneurysm, 14 further supporting the presence of mitochondrial-dependent apoptosis during aneurysm development. The integral relationship between SMC apoptosis and aneurysm is further demonstrated by studies in which apoptosis was attenuated by experimental approaches such as the removal of mast cells, 14 blockage of the angiotensin II (Ang II) signaling, 15 and inhibition of Rho GTPase. 16 However, whether and how SMC apoptosis contributes to aneurysm formation has not been directly addressed.…”
mentioning
confidence: 99%
“…In Marfan syndrome, symptoms such as aneurysms and emphysema reflect excessive TGF-␤ signaling (13). Clinical (12,17) and animal (19,42) studies indicated that the ARBs telmisartan and losartan protected against the progression of aortic aneurysms. Telmisartan was reported to decrease TGF-␤ mRNA levels (43).…”
Section: Discussionmentioning
confidence: 99%
“…From a dental point of view, it is essential to determine the effect of ARBs on the progression of periodontitis. Among ARBs, telmisartan has the longest half-life of any ARB and has 3,000 times higher binding affinity to AT1 than to AT2 (18)(19)(20). In this study, we took advantage of the drug action of telmisartan and examined its effect on the experimental periodontitis model.…”
mentioning
confidence: 99%
“…Some reports have shown that telmisartan and another ARB, valsartan, prevent vascular remodeling through inhibition of oxidative stress, inflammation and degradation of the extracellular matrix independent of their antihypertensive effects. 20,[24][25][26] Heximer et al 9 have reported that responsiveness to another ARB, candesartan, is more sensitive in Rgs2 À/À mice than Rgs2 +/+ mice with regard to its antihypertensive and organ protection effects. Thus, vascular protective effects through inhibition of oxidative stress by low-dose ARB may be exaggerated in Rgs2 À/À mice as a result of its antagonism for excessive AT 1 R signaling.…”
Section: Discussionmentioning
confidence: 99%